Effective Force Stabilising Technique for the Immersed Boundary Method (Communications in Computational Physics, 2023)
The immersed boundary method has emerged as an efficient approach forthe simulation of finite-sized solid particles in complex fluid flows. However, one ofthe well known shortcomings of the method is the limited support for the simulationof light particles, i.e. particles with a density lower than that of the surrounding fluid,both in terms of accuracy and numerical stability.Although a broad literature exists, with several authors reporting different approachesfor improving the stability of the method, most of these attempts introduce extra complexities and are very costly from a computational point of view.In this work, we introduce an effective force stabilizing technique, allowing to extendthe stability range of the method by filtering spurious oscillations arising when dealingwith light-particles, pushing down the particle-to-fluid density ratio as low as 0.04.We thoroughly validate the method comparing with both experimental and numericaldata available in literature.